2016
DOI: 10.1002/eji.201646582
|View full text |Cite
|
Sign up to set email alerts
|

SHP1‐ing thymic selection

Abstract: The development of conventional T cells in the thymus is highly dependent on parsing small differences in TCR affinity for self MHC-peptide, and responding with the induction of cell-survival and differentiation signals (positive selection) or with activationinduced cell death (negative selection). Regulation of TCR signal strength is important in defining the boundary between positive and negative selection [1,2]. TCR ligation leads to phosphorylation of ITAMs on the CD3 complex by Lck kinase, resulting in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…THEMIS (Thymocyte-expressed molecule involved in selection) is a T cell-specific protein which is critical for T cell development, especially CD4SP thymocytes maturation (Allen, 2009; Fu et al ., 2009; Johnson et al ., 2009; Kakugawa et al ., 2009; Lesourne et al ., 2009; Patrick et al ., 2009). Furthermore, it is reported that the interplay between SHP1 and THEMIS is important to regulate the threshold of TCR signal transduction for positive and negative selection during T cell development (Choi et al ., 2017a; Choi et al ., 2017b; Fu et al ., 2013; Gascoigne and Acuto, 2015; Gascoigne et al ., 2016a; Gascoigne et al, 2016b; Mehta et al ., 2018; Paster et al ., 2015). To verify this interaction, immunoprecipitation experiments were performed in both Jurkat and HEK293T cell lines with co-expression of THEMIS and SHP1 WT or DA mutant, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…THEMIS (Thymocyte-expressed molecule involved in selection) is a T cell-specific protein which is critical for T cell development, especially CD4SP thymocytes maturation (Allen, 2009; Fu et al ., 2009; Johnson et al ., 2009; Kakugawa et al ., 2009; Lesourne et al ., 2009; Patrick et al ., 2009). Furthermore, it is reported that the interplay between SHP1 and THEMIS is important to regulate the threshold of TCR signal transduction for positive and negative selection during T cell development (Choi et al ., 2017a; Choi et al ., 2017b; Fu et al ., 2013; Gascoigne and Acuto, 2015; Gascoigne et al ., 2016a; Gascoigne et al, 2016b; Mehta et al ., 2018; Paster et al ., 2015). To verify this interaction, immunoprecipitation experiments were performed in both Jurkat and HEK293T cell lines with co-expression of THEMIS and SHP1 WT or DA mutant, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, one debate regarding the function of THEMIS in T cell development during positive selection is focused on its role in regulating the phosphatase activity of SHP1. Although several groups agree on the essentiality of THEMIS during T cell development through its interaction with SHP1, two contradictory models have been proposed regarding the positive or negative role of THEMIS in moderating the phosphatase activity of SHP1, which leads to a decrease or increase of TCR signaling response accordingly (Choi et al, 2017a; Choi et al, 2017b; Fu et al, 2013; Gascoigne and Acuto, 2015; Gascoigne et al, 2016a; Mehta et al, 2018; Paster et al, 2015). Thus, there is an urgent need to develop a systematic platform to profile the whole spectrum of potential substrates for any given PTP and to further characterize the molecular function of these PTPs within a physiological context.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Shp1 in the development of thymocytes is not yet clear. There have been contradictory studies regarding the involvement of this phosphatase in thymic development ( 23 , 24 , 27 ). As Themis regulates Shp1 activity in the thymus, we initially predicted the phenotype of Shp1-deficient thymocytes to be similar to that of Themis KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work using mice conditionally deficient for Shp1 in the T cell lineage, CD4-Cre, Ptpn6 fl/fl (Shp1 cKO), reported a lack of any significant defect in thymocyte development ( 23 ). However, a more recent study has identified some relatively subtle changes in thymic selection ( 24 , 27 ). We tested the Themis-associated PTP activity in Shp1 cKO thymocytes, finding that in the absence of Shp1, Themis interacts with Shp2 and retains most of the associated phosphatase activity.…”
mentioning
confidence: 99%